Reformulating Land Deed Officials Liability in Tax Document Forgery Cases - Teguh Adhipradana (Law Development Journal, 2026)
This study aims to analyze the legal arrangements regarding the responsibilities of Land Deed Making Officials (PPAT) in the case of falsification of tax documents and formulate fair liability limits. This research uses normative juridical methods with laws and regulations, conceptual, and case approaches. The novelty of this research lies in the introduction of the concept of "reasonable verification standards" as a new legal framework in determining the limits of PPAT's liability. The results of the study show that PPAT cannot be held materially or criminally liable if it has carried out administrative verification according to procedures, but is still deceived by false documents submitted by buyers. The main responsibility lies with the buyer as a taxpayer who deliberately commits forgery. In addition, the absence of an integrated real-time validation system weakens the basis for imposing excessive liability on PPAT. Therefore, this study proposes a reformulation of responsibilities that limits the role of PPAT to administrative and procedural aspects, while material and criminal responsibilities remain imposed on the perpetrator. This reformulation is important to realize legal certainty, justice, and usefulness in the land administration and taxation system.